2017
DOI: 10.5539/jas.v10n1p225
|View full text |Cite
|
Sign up to set email alerts
|

Gompertz and Logistic Models to the Productive Traits of Sunn Hemp

Abstract: Studies on growth models for productive character of sunn hemp are important to know the behavior of the culture. Therefore, the objective of this research was to adjust non-linear models, Gompertz and Logistic, in the description of productive traits of sunn hemp in two sowing periods. Two uniformity trials were performed. The evaluations began on October the 29 th 2014 and December the 16 th 2014, totaling 94 and 76 evaluation days for periods 1 and 2, respectively. After the emergence of the seeds of sunn h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
3
17
1
Order By: Relevance
“…Comparing the estimates of the parameters of the nonlinear models for plant height, between the sowing times in each cultivar, it was verified was no significant effect in the estimates of the parameters in 75.83% of the comparisons (Table 4). This comparison between the estimates of the parameters was found in a study comparing the sowing times of Crotalaria juncea in the Gompertz and Logistic models (Bem et al, 2018). However, in this study a smaller non-significant effect was observed in the estimates of the parameters in the comparisons between the sowing times.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Comparing the estimates of the parameters of the nonlinear models for plant height, between the sowing times in each cultivar, it was verified was no significant effect in the estimates of the parameters in 75.83% of the comparisons (Table 4). This comparison between the estimates of the parameters was found in a study comparing the sowing times of Crotalaria juncea in the Gompertz and Logistic models (Bem et al, 2018). However, in this study a smaller non-significant effect was observed in the estimates of the parameters in the comparisons between the sowing times.…”
Section: Resultssupporting
confidence: 62%
“…He might also predict the moment in which the crop will start to decline in growth, until it reaches the maximum peak, resembling the asymptote of the chosen model. Therefore, according to Bem et al (2018), the period between the maximum point of acceleration and the end of the point of inflection is the best time to infer about management procedures such as fertilization, pest and disease control, and herbicide application, since in this interval the plant will respond efficiently. However, crop management is necessary along the whole period in which the crop is in the field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to observe that the fresh shoot mass (FSM) and the dry shoot mass (DSM) as a function of accumulated solar radiation (ASR), showed dispersion in the sigmoidal shape, justifying the fit of the Gompertz and Logistic models. Bem et al (2018) to compare sowing dates of crotalária juncea.…”
Section: Resultsmentioning
confidence: 99%
“…The nonlinear Gompertz and Logistic models are used to describe plant growth, as they have the same sigmoidal shape of the growth curves. These two models were studied to describe the growth of sunflower (Bem et al, 2018), cocoa (Muniz, Nascimento, & Fernandes, 2017), and coffee cultivar Rubi MG 1192 (Pereira et al, 2014) and were considered adequate.…”
Section: Introductionmentioning
confidence: 99%